Pengaruh Profitabilitas, Financial Leverage dan Size Terhadap Perataan Laba (Income Smoothing) Pada Perusahaan Manufaktur Tekstil dan Garment Yang Terdaftar di BEI Tahun 2012 – 2016 - Rosyidah, Nur; Nugroho, Tatas Ridho; Dwihandoko, Toto Heru (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2019)
Income smoothing is the process of report manipulation earning so that fluctuation can be reduced in earning to a level considered normal by the company. This action is often used by managers to reduce the risk of the company's stock market. Income smoothing actions occur because investors in evaluating company performance often focus on the company's profit in the financial statements published. The purpose of this study is to determine whether there is an effect of profitability, financial leverage, and size on income smoothing. Furthermore, knowing the relationship between t test and f test that can be proved by partial and simultaneous, and to find out the most dominant factors that influence income smoothing. The sample in this study are textile and garment manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2012 - 2016. Data was collected through purposive sampling method. The analysis performed is multiple linear regression, t test, f test, coefficient of determination test by first doing a classic assumption test. The results of this study indicate that Financial Leverage  and size have a significant effect on income smoothing. Profitability has no significance influence on income smoothing.